Assessment of prospective memory in schizophrenia using the Chinese version of the Cambridge Prospective Memory Test: A controlled study. (31st July 2012) - Au, Raymond W.C.; Man, David; Shum, David; Lee, Edwin; Xiang, Yu‐Tao; Ungvari, Gabor S.; Tang, Wai‐Kwong
Abstract Introduction Data on the psychometric assessment of prospective memory (PM) are limited. The Cambridge Prospective Memory Test (CAMPROMPT) and its Chinese version (CAMPROMPT‐C) have been applied to a variety of clinical conditions except for chronic schizophrenia. This controlled study explored the clinical utility of the CAMPROMPT‐C in patients with schizophrenia by comparing their PM performance with that of normal controls. Methods Forty‐four schizophrenia patients and 44 normal controls formed the study sample. Sociodemographic characteristics, PM, retrospective memory, and intelligence were measured in all subjects. Patients' psychopathology was rated with a standardized instrument. Results Patients performed worse than normal controls on both the sum and subscale scores of the CAMPROMPT‐C. Patients had comparable performances in PM subtypes. Bivariate analyses revealed that education level, intelligence, and retrospective memory were associated with PM functions. Discussion The study supports the clinical utility of the CAMPROMPT‐C in chronic schizophrenia and corroborated the significant relationship between PM and education, intelligence, and retrospective memory.